2022
DOI: 10.1186/s42506-022-00110-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of patient safety culture among the staff of the University Hospital for Gynecology and Obstetrics in Alexandria, Egypt

Abstract: Background Patient safety (PS) is a fundamental component of healthcare quality. Patient Safety Culture (PSC) assessment provides an organization with insight of perceptions and attitudes of its staff related to patient safety. In addition, it is meant to improve performance rather than blaming individuals. This study aimed to assess patient safety culture from the health care staff perspective in El-Shatby University Hospital for Gynecology and Obstetrics. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…About two-thirds of nurses (67.4%) in the current study worked an average of 40 to 59 h per week, which indicates a heavy workload on nurses and might lead to more errors that affect the quality of care and patient safety. Two Saudi studies came to similar conclusions [ 20 , 22 ]. They said that insufficient staffing is a common problem that hurts nurses because of heavy workloads and long hours.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…About two-thirds of nurses (67.4%) in the current study worked an average of 40 to 59 h per week, which indicates a heavy workload on nurses and might lead to more errors that affect the quality of care and patient safety. Two Saudi studies came to similar conclusions [ 20 , 22 ]. They said that insufficient staffing is a common problem that hurts nurses because of heavy workloads and long hours.…”
Section: Discussionmentioning
confidence: 55%
“…Compared to the previous studies in Saudi Arabia, the observed positive response rate in this study is comparable to those reported in AlSabaani in the Southern region of Saudi Arabia [ 18 ], while the result is lower than that in Aboufour and Subbarayalu’s study [ 19 ], which reported an average of 67.12% in hospitals in the Eastern region. The variation in the reported average and positive patient safety culture could be attributed to the different hospitals' structures, the organization’s awareness of patient safety culture, hospital experience, size, function, types of services, and samples included in each study [ 20 , 21 ]. This finding suggests that hospital management could consider implementing strategies aiming to teach and promote supervisory behaviors that encourage the nursing staff to report information regarding safety and participate in safety initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…Posting patient's safety standard in all applicable areas was documented in 66.7% and 64.4% of visits in ICU and NICU respectively. Ali et al (12) revealed that patient safety culture among the staff of the University Hospital in Alexandria was 62.1%.…”
Section: Discussionmentioning
confidence: 99%
“…This negative attitude was highlighted in studies conducted in the study settings [ 49 51 ]. Poor prevailing patient safety culture is a another concern explaining missed perioperative nursing care since previous works in the study settings found poor perception of healthcare providers for patient safety culture [ 52 54 ]. Poor staff compliance with patient safety guidelines as well as lack of awareness about risk mitigation are also critical factors explaining the missed care items in our study.…”
Section: Discussionmentioning
confidence: 99%